138k views
5 votes
Make r the subject of this formula
v=3 cubed (square root p+ r)

2 Answers

3 votes

Answer:


\displaystyle r=(v^2 )/(3^(6) )-p

Explanation:


v=3^3(√(p+r) )

Divide both sides by 3³.


(v)/(3^3 ) =(3^3(√(p+r) ))/(3^3)


(v)/(3^3 ) =√(p+r)

Square both sides.


((v)/(3^3 )) ^2 =(√(p+r))^2


(v^2 )/(3^(3 * 2) )=(√(p+r))^2


(v^2 )/(3^(6) )=p+r

Subtract p from both sides.


(v^2 )/(3^(6) )-p=p+r-p


(v^2 )/(3^(6) )-p=r

Switch sides.


r=(v^2 )/(3^(6) )-p

User Enpenax
by
5.0k points
4 votes

Answer:


r = {((v)/(27) ) } ^(2) \: - p

Explanation:


v = {3}^(3) √(p + r) \\ v = 27 √(p + r) \\ (v)/(27) = (27 √(p + r) )/(27) \\


(v)/(27) = √(p + r) \\ {((v)/(27) ) }^(2) = p + r \\ {((v)/(27) ) } ^(2) \: - p = r \\

User Rashi Goyal
by
5.4k points